Purification, Molecular Cloning and Expression of Three Key Saponin Hydrolases from Trichoderma reesei, Trichoderma viride and Aspergillus fumigatus - Jiamin Huang, Yangyang Wang, Linshan Fang, JiaojunJin, Suhui Ye, Wenjing Dun and Yuling Zhu (Nature Environment and Pollution Technology, 2019)
Microbial transformation is an environment-friendly approach to produce diosgenin from natural plant tubers. However, improving the bioconversion efficiency of this process remains a challenge. Saponin hydrolase plays a major role during the transformation. a-rhamnase, b-glycosidase and C3 b-glycosidase have been identified as three key enzymes in the stepwise conversion of saponins to diosgenin. The three enzymes have not been molecularly characterized. Here, a-rhamnase, b-glycosidase and C3 b-glycosidase were purified from Trichoderma reesei, Trichoderma viride and Aspergillus fumigatus, respectively. SDS-polyacrylamide gel electrophoresis showed that the molecular masses of the three enzymes were approximately 60, 36 and 56 kDa, respectively. a-rhamnase could efficiently hydrolyse the terminal rhamnoside on the C3 site in saponins. b-glycosidase could cleave the terminal b-glycoside at the C3 position, while C3 b-glycosidase demonstrated significant affinity to the b-glycoside at the C3 position. The amino acid sequences of the three saponin hydrolases were determined. Reverse transcription-PCR was used to clone the three plasmids with lengths of approximately 1035, 1416 and 1752 bp from the strains and expressed in Escherichia coli. The recombinant saponin hydrolases from the recombinant strains also demonstrated the hydrolysing of rhamnoside and glycosides of saponins similar to those of the wild-type hydrolases from T. reesei, T. viride, and A. fumigatus. The findings could facilitate the construction of recombinant cells by gene fusion to produce diosgenin from plant tubers.